Diarrheagenic Escherichia coli and Shigella Strains Isolated from Children in a Hospital Case-Control Study in Hanoi, Vietnam - Hien, Bui Thi Thu (American Society for Microbiology (ASM), 2008)
This case-control study detected and characterized Shigella and diarrheagenic Escherichia coli (DEC) types among Vietnamese children less than 5 years old. In 249 children with diarrhea and 124 controls, Shigella spp. was an important cause of diarrhea (P < 0.05). We used multiplex PCR and DNA probes to detect enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAggEC), enteropathogenic E. coli (EPEC), attaching and effacing E. coli (A/EEC), verocytotoxin-producing E. coli (VTEC), and enterotoxigenic E. coli (ETEC). The prevalences of DEC in the diarrhea and control groups were 25.7 and 10.5%, respectively. In 62 children with diarrhea, 64 DEC strains included 22 EAggEC (8.8%), 2 EIEC (0.8%), 23 A/EEC (9.2%), 7 EPEC (2.8%), and 10 ETEC strains (4.0%). Among controls, 13 DEC strains included 5 EAggEC strains (4.0%), 7 A/EEC strains (5.6%), and 1 EPEC strain. The characterization of DEC by serotypes, antimicrobial susceptibility patterns, virulence genes, and pulsed-field gel electrophoresis showed the occurrence of many different and highly heterogenic DEC subtypes, but common serotypes were found among ETEC, EIEC and EPEC, respectively. Serotyping was used to distinguish between A/EEC and EPEC. However, A/EEC, EPEC, and EAggEC were isolated at high frequency from both cases and controls. Further in-depth studies are needed to better understand important virulence factors of DEC, especially A/EEC, EPEC, and EAggEC.